A comparison among innovative plants for high quality extra‐virgin olive oil production. (8th July 2020) - Altieri, Giuseppe; Genovese, Francesco; Matera, Attilio; Di Renzo, Giovanni Carlo
Abstract: BACKGROUND: The cleaning operation of extra‐virgin olive oil (EVOO), subsequent to its extraction, is generally performed by means of a vertical disc stack centrifuge separator causing qualitative damage due to increased oxidative alterations. However, previous works have demonstrated the great opportunity that settling represents in order to improve the EVOO quality performing the separation operation with minimal qualitative damage. RESULTS: A new patented prototype device (ROTASED, RS) has been used in the cleaning operation of extra‐virgin olive comparing physical and chemical characterization of EVOO after 48 h from extraction and after 180 days of shelf‐life. In addition, the results have been compared with those obtained using an assisted sedimentation (AS) plant and an enhanced sedimentation plant by hydrocyclone (H) from previous authorsʼ works, in order to assess the improvement of EVOO quality that could be attained with respect to the use of the vertical disc stack centrifuge separator. CONCLUSION: The results show that after 48 h of storage the tested patented prototype device seems to be preferable, however, after 180 days of storage, the difference between H and RS device results similar in terms of improvement of the final olive oil quality. In addition, the method of principal component analysis can be used to evaluate the suitability of an olive cv. in terms of quality of extracted oil. © 2020 Society of Chemical Industry